2006
DOI: 10.1002/lsm.20280
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effects of combined radio-frequency current and a 900 nm diode laser on leg blood vessels

Abstract: The success of the treatment, minimal side effects, and patient comfort suggest that this combination is an effective, safe technique for leg vein treatment. When compared to previous studies using diode laser alone, the very low fluence needed to achieve vessel clearance emphasizes the role of RF energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The combination of IR laser and RF current has already been proposed as an efficacious treatment for leg vein coagulation (22) and has been reported to achieve rejuvenation-related effects (23). It was therefore interesting to examine the combination of RF, IR light and mechanical massage and suction as proposed in previous studies, but comparatively examining the tissue through an intra-patient split treatment, assigning subjective and objective scores and also checking the histological effects on tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of IR laser and RF current has already been proposed as an efficacious treatment for leg vein coagulation (22) and has been reported to achieve rejuvenation-related effects (23). It was therefore interesting to examine the combination of RF, IR light and mechanical massage and suction as proposed in previous studies, but comparatively examining the tissue through an intra-patient split treatment, assigning subjective and objective scores and also checking the histological effects on tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Schaffer et al irradiated the planta pedis of healthy volunteers [12], Teggi treated patients with Meniere’s disease [26], Hirschl treated patients with Raynaud’s phenomenon [27], and Trelles irradiated leg blood vessels with success [16]. Tullberg exposed the masseter muscle to a gallium-aluminium-arsenide laser because of muscle pain and demonstrated an increase in microcirculation [28].…”
Section: Discussionmentioning
confidence: 99%
“…There have also been reports of intravenous laser blood irradiation used to good effect in body-building athletes [15]. Positive effects have observed during laser therapy of venous ulcers (900 nm diode laser, pulsed) combined with radiofrequency (RF) current [16]. …”
Section: Introductionmentioning
confidence: 99%
“…• When combining the 900 nm diode with bipolar radiofrequency, Trelles et al demonstrated a vessel clearance rate greater than 75 % at 6 months in 50 % of the patients [ 36 ].…”
Section: Long-pulse Infrared Alexandrite Lasermentioning
confidence: 99%